Analisis Keuntungan Rumah Makan Muslim Ummi Hidayah Di Kawasan Boulevard Tondano Kabupaten Mianahasa - Wahibu, Safira; Pangemanan, Lyndon Reindhart Jacob; Mandei, Juliana Ruth (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the business profits of Ummi Hidayah Restaurant in the Tondano Boulevard Area, Minahasa Regency. The data used in this study are primary data and secondary data, data collection techniques used using descriptive analysis, namely analyzing, describing, and interviews. Data analysis used is using the calculation of costs, revenues and profits. Based on the results of the study, it is obtained that the amount of profit of the ummi hidayah Muslim restaurant business in the Tondano boulevard area can be categorized as a profitable business with a service profit and total revenue of Rp17,860,046 per month.